2023
DOI: 10.1055/a-2003-5983
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Pregnancy, Birth and Puerperium. Guideline of the DGGG and DGPM (S2k-Level, AWMF Registry Number 015/092, March 2022)

Abstract: Objective This S2k guideline of the German Society for Gynecology and Obstetrics (DGGG) and the German Society of Perinatal Medicine (DGPM) contains consensus-based recommendations for the care and treatment of pregnant women, parturient women, women who have recently given birth, and breastfeeding women with SARS-CoV-2 infection and their newborn infants. The aim of the guideline is to provide recommendations for action in the time of the COVID-19 pandemic for professionals caring for the above-listed groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 115 publications
(232 reference statements)
0
6
0
Order By: Relevance
“…Adjusted screening testing increased over 75% in neonates admitted to the NICU in accordance with that guideline. Clinical management of mothers also changed when an increased risk of thromboembolic events due to SARS-CoV-2 infection, especially during pregnancy, became apparent 10 . After that, CRONOS recorded a definite increase in heparin prescription to pregnant women with symptomatic SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adjusted screening testing increased over 75% in neonates admitted to the NICU in accordance with that guideline. Clinical management of mothers also changed when an increased risk of thromboembolic events due to SARS-CoV-2 infection, especially during pregnancy, became apparent 10 . After that, CRONOS recorded a definite increase in heparin prescription to pregnant women with symptomatic SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve those goals, intensive, personal, and preferably one-on-one obstetric care is key [22,23]. Over time, it was shown that vaginal deliveries of SARS-CoV-2-positive women were not generally associated with a higher risk of adverse events for mother or newborn [10,15,24]. In recent analyses, CRONOS and others found that the highest risk of suffering from severe COVID-19 occurred when infected around 30 weeks of gestation [11,19].…”
Section: Obstetric Managementmentioning
confidence: 99%
See 3 more Smart Citations